2014
DOI: 10.1089/fpd.2013.1718
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Treatment of Both Sides of Raw Chicken Breasts with an Atmospheric Pressure Plasma Jet for the Inactivation of Escherichia coli

Abstract: Atmospheric pressure plasma (APP) is an emerging nonthermal microbial inactivation technique. In this study, agar and raw chicken breast were inoculated with Escherichia coli and treated with an APP jet based on cold arc plasma. The aim of this study was to investigate the optimum conditions for the plasma treatment of an APP jet in order to maximize the efficiency of E. coli inactivation. The combination of N2+O2 (10 standard cubic centimeters per minute) and a longer treatment time (10 min) resulted in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Recent studies have proposed cold plasma as a tool to enhance the production yield in chicken farms, through vaccine production, growth and reproduction enhancement (Wang; et al., ; Zhang et al., ; Zhang, Do, et al., ; Zhang, Huynh, et al., ; Zhang, Wang, et al., ), and to assure the safety of the poultry products (Aly, ; Apostol et al., ; Dirks et al., ; Georgescu et al., ; Lee et al., 2011, , ; Ragni et al., ; Rossow et al., ; Wang et al., ; Yong et al., ; Figure ). This wide range of potential application is because of the presence of reactive species and photons and the consequent chemical reactions that these components may induce in the treated product.…”
Section: Nonthermal Plasma and Poultry Industrymentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have proposed cold plasma as a tool to enhance the production yield in chicken farms, through vaccine production, growth and reproduction enhancement (Wang; et al., ; Zhang et al., ; Zhang, Do, et al., ; Zhang, Huynh, et al., ; Zhang, Wang, et al., ), and to assure the safety of the poultry products (Aly, ; Apostol et al., ; Dirks et al., ; Georgescu et al., ; Lee et al., 2011, , ; Ragni et al., ; Rossow et al., ; Wang et al., ; Yong et al., ; Figure ). This wide range of potential application is because of the presence of reactive species and photons and the consequent chemical reactions that these components may induce in the treated product.…”
Section: Nonthermal Plasma and Poultry Industrymentioning
confidence: 99%
“…Therefore, the results of this study might be different from that of the industrial decontamination of poultry products wherein the microorganisms are mainly located on the chicken skin or eggshell with special topography and different chemical composition (for example, different protein, fat, and moisture levels). Therefore, food scientist assessed the decontamination effects of cold plasma on chicken meat (Dirks et al., ; Lee et al., ; Myers et al., ; Noriega, Shama, Laca, Díaz, & Kong, ; Rossow et al., ; Wang et al., , ; Yong et al., ) and egg (Apostol et al., ; Georgescu et al., ; Lee et al., ; Ragni et al., ; Wan, Chen, Pankaj, & Keener, ; Figure ).…”
Section: Nonthermal Plasma and Poultry Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…When treating with a 324 plasma jet, exposure of both sides of the meat surface to plasma is recommended for 325 ensuring treatment uniformity and higher inactivation. It has been shown that exposure of 326 each side of chicken breast to plasma for 2.5 min resulted in higher inactivation of E. coli 327 than 5 min treatment on single side (Yong, et al, 2014). 328…”
Section: Effect Of Gas Composition 260mentioning
confidence: 99%